Biatrial drainage of right superior caval vein with preferential streaming into the left atrium. (17th June 2019) - Abu-Anza, Omar; Ashwath, Ravi
Abstract: Biatrial drainage of the right superior caval vein is an extremely rare cardiac anomaly that generally presents in childhood. We present a case of anomalous connection of the right superior caval vein with superior sinus venosus atrial septal defect and partial anomalous pulmonary venous return in a 5-month-old male presenting with unexplained cyanosis and hypoxia.